ISLAMIC ASPECTS IN MAPPETTUADA TRADITION FOR CROSS-CULTURAL PERFORMANTS (Anthropolinguistics Approach) - Ansar, Fithrah Auliya (Elite : English and Literature Journal, 2016)
Mappetuada was the fifth step of wedding proposing tradition in South Sulawesi. The aim of this research was to acknowledge the reader about how the bugis people used their language in Proposing woman in mappetuada tradition. Many religious symbols were used in Bugis local custom in order to perform their identity as a part of religious people. Islam, the most majority religion in Indonesia, is always appeared in each tribes’ activities through appearance or even untterance. This research is a part of Anthropholinguistics research. The theory of Functional analysis is used in finding the voices of speaker in using their languages. The analysis focused on various features of Islamic symbols in people utterances and appearances related to the cultural performance. The additional theory about Bakhtinian dialogism was used in order to find the features which are related and different among the people in mappetuada tradition. The result showed the features of islamic performance used by each performants from different cultural background in mappettuada tradition. The islamic cues were not only found in non- verbal signs but also existed in verbal utterances.